Entre a guerra, o pós-guerra e um outsider: as narrativas mnemônicas de mangás pós-Segunda Guerra Mundial - Zanoni, Antonio Augusto (2021)
The manga market has been present in many countries around the world for some time now. However, its global market explosion is very recent (about 40 years), and studies involving manga as a historical object are much more recent. For the purposes of this work, we will not return to manga and its structures before World War II, but will focus on its contemporary form. Therefore, the intention is to first address aspects of Japanese history that contribute to the research. Subsequently, we will observe the aporias of memory in contact with our object of study. In a third moment, we will re-present analyses and themes that link history, memory and manga based on other research, largely still displaced from Brazilian studies on manga. Finally, we will seek to analyze the narratives produced by three manga authors, who experienced the war in different ways, namely: Shigeru Mizuki, with the four volumes of Showa and the manga March to Death; Yoshihiro Tatsumi, in the manga Good-bye; and George Takei, in the manga They called us enemy. To this end, the research is conducted in order to understand that images, like written language, are narratives that need to be understood in their context. In our case, when we speak of narrative, we think of the image together with the written text. In our context, it became possible to observe that mangas are essential historical sources for thinking about the history of Japan, since they are produced by the same agents who experienced the different faces of the war. Furthermore, memory, history and trauma were understood as key concepts for observing Japan after the Second World War based on the analysis of the mangas studied, since they were created based on traumatic memories, which remain in the form of mnemonic wounds. As was verified, the mnemonic narratives found in the mangas of our authors are not entirely negative and traumatic. We observe that, even in difficult times, the human spirit was able to find joy and comfort in small things, as in the case of Shigeru Mizuki, when he was saved and fed by the natives, or in the narrative of George Takei, who listened to stories from his father with the intention of preserving a pleasant environment for his children, even in complex circumstances. However, it was also possible to observe that the events caused by the Second World War and its consequences never ceased to torment the families that, in some way, found themselves involved. Finally, even if it is covered up in Tatsumi's manga, as it is made explicit in Takei and Mizuki's mangas, the fact that war is an accumulation of suffering that never ceases to be present in the daily lives of those who were involved, resulted in the production of narratives that appeal to the reader to avoid violence and prejudice at all costs.